The Prevalence of Occult Omental Metastases in Patients with Epithelial Ovarian Cancer - Hariyono Winarto; Ken Indra (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: Studies regarding omentectomy on epithelial ovarian cancer are scarce with conflicting results; this study is aimed to investigate the prevalence of occult metastases in patients with epithelial ovarian cancer of the omentum. Methods: A cross-sectional study design was used by evaluating the medical records of surgically staged ovarian cancer patients in Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia during the period of January 2009 to December 2015. Results: A total of 51 subjects were involved in this study. One (2%) of 51 subjects was found to have occult metastases in the omentum. The prevalence of metastases of early stage epithelial ovarian cancer in 2009-2015 is 33.3% (17 out of 51 subjects), whereas the omental involvement is found only in 2% subjects (1 out of 51). Conclusion: The prevalence of occult metastases of early stage epithelial ovarian cancer in Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia, from 2009-2015 in 2% (1/51 subjects). [Indones J Obstet Gynecol 2018; 6-2: 119-122] Keywords: cancer, epithelial, metastases, omentum, ovarian cancer, ovary, prevalence